The Influence Of Liquidity And Company Size On The Quality Of Profits In The Pharmaceutical Sector On The Indonesian Stock Exchange In 2019 – 2022 - Siahaan, Septony B; Simanjuntak, Arthur; Simanjuntak, Wesly Andri; Januardi Mesakh; Silalahi, Mulatua; Sibarani, Christofer Parmahan (Jurnal Ilmiah Accusi, 2024)
This research aims to find out and analyze how much influence liquidity and company size have on the profit quality of the pharmaceutical sector listed on the Indonesia Stock Exchange (BEI) in 2019 - 2022. The population in this research is 10 Pharmaceutical Sector Companies listed on the Indonesia Stock Exchange (BEI) in 2019 - 2022. The sampling method in this research is the Non-Probability Sampling method with a Purposive Sampling technique of 8 pharmaceutical companies with four years of observation. and the data used is secondary data sourced from annual reports of pharmaceutical companies via the website www.idx.co.id. The data analysis method used in this research is the multiple linear regression analysis method. Partial results show that liquidity has a significant negative effect on earnings quality. Company size has an insignificant negative effect on Earnings Quality. The results with the F test show that Liquidity and Company Size simultaneously do not have a simultaneous effect on Earnings Quality. Test Results The coefficient of determination shown from the Adjust R-Square value is 16.4%. This means that 16.4% of the dependent variables are Liquidity and Company Size while the remaining 83.6 is influenced by other variables outside of this research model